Respon Pertumbuhan dan Produksi Tanaman jagung Manis ( Zea mays Saccharata Strut ) Pada Lahan Kering Masam Terhadap Pemberian Kompos Limbah Perkebunan dan Pupuk N, P dan K - Moelyohadi, Yopie; Alatas, Andi (Fakultas Pertanian, Program Studi Agroteknologi, 2025)
Sweet corn (Zea mays Saccharata Sturt) is one of the food crops widely consumed by the community, because it has a sweet taste and high nutritional value and has a fairly high economic value. In an effort to increase the productivity of sweet corn plants, appropriate cultivation technology input is needed, especially in the provision of fertilizers. Corn yields can be increased with appropriate fertilization, both in terms of dosage and time and the type of fertilizer given. Empty oil palm bunches (tangkos), Blotong (sugarcane waste) and legume cover crop compost (LCC) are wastes produced from the cultivation and post-harvest activities of oil palm plantations that can be used to increase the availability of organic matter and soil fertility in agricultural land. Based on the results of the diversity analysis, it shows that the treatment of providing types of plantation waste compost and the treatment of N, P, and K fertilization levels have a significant to very significant effect on each variable observed. Meanwhile, the interaction between the type of plantation waste compost and the treatment of N, P, and K fertilization levels has no significant effect on each variable of sweet corn growth and production on dry acidic land.